The Unique Challenge to The Contemporary Corporate Reporting of Achieving Efficiency in The Disclosure of Climate-Related Issues - Hristina Oreshkova (International Business and Accounting Research Journal, 2023)
Over the recent decades, climate change has been rising. The problems caused by the intensifying climate change are unique. The climate change process creates an existential threat to humans and all living beings interrelated with another risk arising from the crisis caused by the observed biodiversity deterioration and environmental degradation. The compound and complicated coexisting impacts of both factors on people, biodiversity, and economic entities and sectors pose unprecedented challenges to humankind. The unfavorable present-day circumstances and effects due to climate change require adequate governmental, managerial, and administrative strategies, policies, and activities for achieving sustainable, fair, and resilient growth. Moreover, phenomena and processes indicating climate change are developing on a global scale that gives rise to discussion, highlights, and justifies the existing need for meaningful climate-related disclosures through the system of corporate reporting. The necessity of trustworthy, transparent, and reliable disclosures on climate-related matters and inherent risks and opportunities focused on climate-change mitigation and adaptation is a problem of crucial importance to the present article. The relevance of climate-related disclosures as a significant part of present-day corporate reporting proves to be of great importance in achieving disclosure efficiency. The author aims to highlight, discuss and justify the necessity of a responsible approach to conducting an adequate disclosure policy and providing meaningful and consistent disclosures concerning climate-related matters, risks and opportunities considered a significant part of corporate reporting, and to substantiate why probable benefits for a sustainable future can be expected, not only for the company. The terminology of the research is in the field of financial and non-financial reporting and their numerous regulatory frameworks that are not fully aligned yet. Heuristic methods of knowledge such as analysis and synthesis, induction and deduction, descriptive approach, and techniques such as observation, analogy, comparison, and others are applied in the research process which is crucial to achieving the author’s objective.